The death of a neurotrauma trial lessons learned from the prematurely halted randomized evaluation of surgery in elderly with traumatic acute subdural hematoma (RESET-ASDH) trial - R.D. Singh; J.T.J.M. van Dijck; T.A. van Essen; H.P. Nix; R.J.G. Vreeburg; H.F. den Boogert; G.C.W. de Ruiter; B. Depreitere; W.C. Peul (Brain and Spine)
Introduction: Acute subdural hematoma (ASDH) due to traumatic brain injury (TBI) constitutes an increasing global health problem, especially in the elderly population. Treatment decisions on surgical versus conservative management pose a neurosurgical dilemma. Large practice variation exists between countries, hospitals, and individual neurosurgeons, illustrating the presence of ‘clinical equipoise’. The RESET-ASDH trial aimed to address this dilemma but was terminated prematurely due to insufficient patient recruitment. Research question: What factors may have contributed to the premature discontinuation of the RESET-ASDH trial? Materials and methods: The RESET-ASDH was a multicenter randomized controlled trial (RCT) comparing functional outcome at 1 year after early surgery or an initial conservative treatment in elderly patients (≥65 years) with a traumatic ASDH. Logs of registry data, medical-ethical approval timelines and COVID-19 related research documents were analyzed. Furthermore, non-structured interviews with involved clinical research personnel were conducted. Results: The concept of clinical equipoise was broadly misinterpreted by neurosurgeons as individual uncertainty, hampering patient recruitment. Also, the elderly target population complicated the inclusion process as elderly and their informal caregivers were hesitant to participate in our acute surgical trial. Moreover, the COVID-19 pandemic added additional hurdles like delayed medical-ethical approval, a decline in eligible patients and repeated trial halts during the peaks of the pandemic. Discussion and conclusion: The premature termination of the RESET-ASDH study may have been related to the trial’s methodology and target population with an additional impact of COVID-19. Future acute neurosurgical trials in elderly may consider these challenges to prevent premature trial termination.